QASE-Based Case Study Learning for Enhancing Students’ Critical Thinking Skills on Socio-Environmental Issues: The Case of Forest and Peatland Fires - Wahyuni, Resma; Yustina; Hasibuan, Saberina (Jurnal Paedagogy, 2026)
This study aims to analyze the effect of QASE-based case study learning on students’ critical thinking skills in addressing peatland fire problems. This study employed a quantitative approach using a pre-experimental one-group pretest–posttest design to examine the effectiveness of QASE-based case study learning in improving students’ critical thinking skills. The sample was selected using purposive sampling, involving students enrolled in environmental science and disaster mitigation courses, as well as first-year students. A total of 105 students from the University of Riau participated in this study. Data were collected using Higher-Order Thinking Skills (HOTS) test instruments and observation sheets. The data were analyzed statistically using N-Gain analysis and a t-test. The results showed an improvement in students’ critical thinking scores, with the mean pretest score increasing from 69.74 to a mean posttest score of 87.28. The overall N-Gain score for students’ critical thinking skills was 0.57, which was categorized as moderate. Among the critical thinking indicators, the ability to synthesize showed the most significant improvement in classes A and B. Furthermore, the t-test results showed a significance value of p < 0.05, indicating that QASE-based case study learning was effective in improving students’ critical thinking skills in environmental learning. These findings suggest that the QASE model can be implemented as an alternative case-based learning strategy to enhance students’ Higher-Order Thinking Skills (HOTS), particularly in addressing environmental issues such as peatland fires.